Treatment of traumatic ulcer induced by fixed orthodontic appliance: a case report - Yuli Fatzia OSSA; Khairiyah ULFAH; Rizki Rachmayani SITINJAK (Journal of Syiah Kuala Dentistry Society, 2022)
Orthodontic treatment aims to improve the oral health of the patient. Still, orthodontic treatment canalso cause problems in the oral cavity, such as the appearance of traumatic ulcers caused by the use of orthodonticappliances. The following describes a chronic traumatic ulcer in a patient using fixed orthodontic appliances. CaseReport: A female patient aged 22 years complained of thrush after using braces. Clinical examination revealed asingle ulcerated lesion on the right buccal mucosa of the upper molar region adjacent to the buccal tube of theorthodontic appliance. The patient was then treated with topical corticosteroids and chlorhexidine gluconate. Thepatient was also consulted by an orthodontic specialist for further treatment using orthodontic wax to help protectagainst friction between the wires and the mucosa. The lesions healed on the third visit.: Orthodontic treatmentoften causes injuries to the oral mucosa. It is because the orthodontic appliances used can rub against the oralmucosa so that they are very susceptible to causing traumatic ulcers. Traumatic ulcers arising from orthodontictreatment are generally chronic, requiring comprehensive treatment to reduce patient complaints. Conclusion:Treatment of chronic traumatic ulcers due to the use of fixed orthodontic appliances should be carried outcomprehensively by involving an oral medicine specialist and an orthodontist to provide maximum treatment fortraumatic ulcers and reduce patient complaints.KEYWORDS: Traumatic Ulcer, Orthodontic Appliance, Treatment